Influence of PANi Additions on methanol sensing properties of ZnO thin films - Mohammad Hafizuddin Hj Jumali,; Norhashimah Ramli,; Izura Izzuddin,; Muhamad Mat Salleh,; Muhammad Yahaya, (Universiti Kebangsaan Malaysia, 2011)
The influence of PANI additions on methanol sensing properties of ZnO thin films at room temperature had been investigated. Commercial polyaniline powder (PANI) was mixed into 3 mL ZnO solution in five different weight percentages namely 1.25, 2.50, 3.75, 5.00 and 6.25% to obtain ZnO/PANI composite solutions. These solutions were spin coated onto glass substrate to form thin films. Microstructural studies by FESEM indicated that ZnO/PANI films showed porous structures with nanosize grains. The thickness of the film increased from 55 to 256 nm, proportionate to increment of PANI. The presence of 2 adsorption peaks at ~310 and ~610 nm in UV-Vis spectrum proved that addition of PANI has modified the adsorption peak of ZnO film. Methanol vapour detection showed that addition of PANI into ZnO dramatically improved the sensing properties of the sensor. The sensors also exhibited good repeatability and reversibility. Sensor with the amount of PANI of 3.75 wt% exhibited the highest sensitivity with response and recovery time was about 10 and 80 s, respectively. The possible sensing mechanism of the sensor was also discussed in this article.